TikTok’s utilization as the Pangandaran tourism promotion media during COVID-19 pandemic - Widyaswara, Safira; Arifin, Hadi Suprapto; Prasanti, Ditha (Manajemen Komunikasi, 2023)
This article aims to find out the use of TikTok social media as a promotional medium for Pangandaran Tourism during the COVID-19 pandemic, carried out by the @kelilingpangandaran account. This study uses a qualitative method. Data was collected by in-depth interviews with eight informants and observations of the social media accounts for two months. The results and discussion in the study were relevant to Berger and Luckman’s theory of social construction. This research found a social construction process carried out by the @kelilingpangandaran account. This process uses TikTok social media through audio-visual content packaged creatively and trends to attract more attention. In addition, the TikTok feature is used to facilitate the spread of promotions. The use of Tiktok social media as a promotional medium for Pangandaran Tourism was carried out because it saw the advantages and opportunities that Tiktok social media could utilize to increase promotion. During the tourism promotion activities carried out during the COVID-19 pandemic, of course, experienced various obstacles, but the @kelilingpangandaran account has a strategy to continue maintaining Pangandaran Tourism’s existence. It is even used as a good opportunity to get wider engagement. These processes are included in the construction, which was built to influence the audience to be interested in visiting tourism in Pangandaran during the COVID-19 pandemic.